Voice and Silence as Immediate Consequences of Job Insecurity - Lopez-Bohle, S; Muñoz-Medina, L (Emerald Group Holdings Ltd., 2020)
Purpose: The purpose of this paper is to examine the weekly effects of job insecurity on employee voice and silence. Specifically, the authors argue that because employment fulfils important needs, employees’ needs are less fulfilled when they feel that their job is at risk (i.e. high job insecurity). Consequently, the authors argue that employees engage in less voice and more silence because when employees’ needs are not fulfilled, they are less committed to the organization and/or protect their personal resources. Design/methodology/approach: The authors tested their hypotheses in a five-week long diary study among 97 employees. Findings: The authors found that employees reported lower need fulfilment in those weeks and the week after job insecurity was higher, which, in turn, decreased employee voice and increased employee silence in those weeks and the week after. Research limitations/implications: The study shows that feelings about one’s job insecurity fluctuate from week to week and that the weekly negative effects associated with increased job insecurity can be explained from a needs fulfilment perspective. The study also highlights the importance of studying voice and silence simultaneously. Practical implications: Managers could indirectly increase employees’ voice and decrease employees’ silence by reducing feelings of job insecurity to increase employees’ feelings of predictability of and control over their future. Originality/value: The authors studied short-term effects of job insecurity on both employee voice and silence, and examined need fulfilment as an underlying mechanism to explain the effects of job insecurity. © 2020, Emerald Publishing Limited.